Interações multimodais em uma sala de aula de biologia - Vanessa Avelar Cappelle Fonseca (2014)
This study aimed to characterize how an experienced biology teacher uses multiple modes of communication with the intention of introduce students to the ways of conceive and interpret biological phenomena. For that, our theoretical framework was Social Semiotics and studies in the field of Multimodality. This perspective involves considering the contribution of each mode of communication (composed by words, or gestures, or actions, etc.) in the interaction between a biology teacher and her students, but also the orchestrated use of these modes. To contextualize and justify this research problem we present a literature review, which highlights the need to investigate the role of different semiotic modes in classroom interactions. We conducted our study over a 3-month period at a public federal school devoted to technical training. Classroom lessons were audio and video-recorded to facilitate the process of transcribing, and field notes also played an important role. Relying on Social Semiotics, we designed a unit of analysis, the Communicative Act, which allowed us to understand how modes of communication such as gesture, proxemics, movements of the head, direction of gaze, actions on objects, body posture, among others, have specific contributions to the interactions in the classroom. In addition, we studied the effects of the combined use (orchestration) of these modes. In response to our questions, the analytic scheme that guide the analysis of multimodal interactions enable us to say that: (1) communicative modes, other than language, were particularly relevant in the lessons selected for the study; (2) modes of communication fulfilled very specific functions that were consistent with the affordances and constraints that are characteristic to them as means for the expression of ideational, interpersonal and textual meanings; (3) the orchestration of communication modes performed by the teacher is consistent with the rhetorical intentions that seem to have guided the communicative acts which allow us to characterize her as a qualified communicator in the use of multiple modes of communication to introduce students to the ways of conceive and interpret biological phenomena. Therefore we believe that the analysis contributed to the design of a more accurate picture of the importance not only of words but of multiple modes of communication in Biology teaching and learning. In the closing remarks, we discuss some implications of our findings for educational research and practice.